Energy Hole Minimization with Field Division for Energy Efficient Routing in WSNs - Kamran Latif; Nadeem Javaid; Malik Najmus Saqib; Zahoor Ali Khan; Umar Qasim; Basharat Mahmood; Manzoor Ilahi (International Journal of Distributed Sensor Networks)
We analyze performance of famous cluster based routing protocols and identify the factors affecting energy consumption in wireless sensor networks (WSNs). From theoretical and experimental analysis, it is observed that communication distance and cluster node density are the major sources in the formation of energy and coverage holes. To overcome these deficiencies, we propose a new hybrid approach of static clustering and dynamic selection of cluster heads. We also conduct a comprehensive energy consumption analysis of our technique with selected existing ones. Simulation results show that the proposed technique is relatively better in terms of energy holes minimization and network lifetime prolongation.